2015
DOI: 10.1161/strokeaha.114.007482
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-424 Protects Against Focal Cerebral Ischemia and Reperfusion Injury in Mice by Suppressing Oxidative Stress

Abstract: 513I schemic stroke is one of the leading causes of death and disability in the world, resulting from the disruption of blood supply to the brain. Intervention requires the restoration of blood flow, which can lead to reperfusion injury. Oxidative stress is thought to be the primary event during this process 1 because reperfusion stimulates an overproduction of reactive oxygen species (ROS), such as hydrogen peroxide (H 2 O 2 ), which leads to the oxidation of proteins, lipids, and DNA and can induce cell prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(112 citation statements)
references
References 36 publications
(50 reference statements)
3
102
0
5
Order By: Relevance
“…Oxidative stress is a core pathological component of brain ischemiareperfusion injury causing neuronal malfunction and cell death [32][33][34]. Several miRNAs have been reported to be involved in the cellular response to oxidative stress via the antioxidant defense system [22,24]. As expected, we found that treatment with miR-93 antagomir reduced ROS and MDA levels in the ischemic brain of I/R mice, and increased the SOD activity as well as the expression of HO-1 and Nrf2.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Oxidative stress is a core pathological component of brain ischemiareperfusion injury causing neuronal malfunction and cell death [32][33][34]. Several miRNAs have been reported to be involved in the cellular response to oxidative stress via the antioxidant defense system [22,24]. As expected, we found that treatment with miR-93 antagomir reduced ROS and MDA levels in the ischemic brain of I/R mice, and increased the SOD activity as well as the expression of HO-1 and Nrf2.…”
Section: Discussionsupporting
confidence: 78%
“…miR-93 antagomir (100 μm) or the control (100 μm) were mixed with Lipofectamine RNAiMAX Transfection Reagent (Invitrogen, Carlsbad, CA) and incubated at room temperature for 30 min; 7 μL of the mixture was injected into the right lateral ventricle and the needle was kept in the place for 10 min before the MCAO [22]. The injection position was at the point of 0.5 mm posterior to bregma, 1.0 mm lateral to bregma, and 3.5 mm below the skull surface.…”
Section: Intracerebroventricular Injection Of Mir-93 Antagomirmentioning
confidence: 99%
“…Neural stem/progenitor cells Promote proliferation miR-25 [12]; miR-137 [13]; miR-184 [14]; miR-195 [15] Induce differentiation miR-9, siRNA-TLX [16]; let-7d [17]; miR-137 [13]; miR-184 [14]; miR-195 [15]; miR-34a [18]; lncRNA-BDNF-AS, siRNA-BDNF-AS [19] Mesenchymal stem cells Induce differentiation miR-9 [20]; miR-124 [21] Reduce differentiation miR-128 [22] Neuronal cells Inhibit cell death miR-223 [23]; miR-181c [24]; miR-592 [25]; miR-424 [26]; miR-23a-3p [27]; miR-23a/b, miR-27a/b, siRNA-Apaf-1 [28] Promote cell death miR-134 [29]; miR-200c [30]; miR-30a/b [31][32][33]; miR-124 [34]; miR-711 [35] Regulate degeneration and apoptosis miR-20a [36]; miR-29b [37]; miR-146a, siRNA-miR146a [38] Promote neurite outgrowth miR-7 [39]; miR-21 [40]; miR-222, siRNA-PTEN [41]; miR-8 [42]; miR-431 [43]; miR-145 [44]; lncRNA-uc.217 [45]; miR-138, siRNA-SIRT1 [46] Microglial cells Inhibit inflammation let-7c [47]; miR-124, siRNA-C/EBP-α [48] Promote pro-inflammation miR-155 [49] Inhibit activation let-7c-5p [50] Astrocytes P...…”
Section: Nervementioning
confidence: 99%
“…MiR-424 therapy prevents infarct volume and neuronal apoptosis, reduces the levels of reactive oxygen species (ROS) and malondialdehyde (MAD), and enhances the activities of the antioxidant enzyme SOD. All the results suggest that miR-424 has protective effects against oxidative stress [15]. On the other hand, the nuclear factor, erythroid-derived 2-like 2 (Nrf2), is a redox-sensitive transcription factor and related with inflammatory disease [16, 17].…”
Section: Introductionmentioning
confidence: 99%